Blood and germs : the Civil War battle against wounds and disease - Jarrow, Gail (Jarrow, Gail. Medical fiascoes series., 2020)
Explores the the science and history of medicine during the Civil War. Discusses the damage inflicted by bullets and artillery shells, the microbes and parasites that were prevalent in the military camps and prisons, and the doctors and nurses who treated the soldiers. Also examines the innovations in medical care that emerged from the four-year conflict, including surgical techniques, medicines, and improved patient care.